1979
DOI: 10.1139/f79-075
|View full text |Cite
|
Sign up to set email alerts
|

Net Entanglements of Baleen Whales in the Inshore Fishery of Newfoundland

Abstract: This paper documents net entrapments of baleen whales in the inshore waters of Newfoundland and Labrador. The species involved are principally minke whales (Balaenoptera acutorostrata) and humpback whales (Megaptera novaeangliae). Finback whales (Balaenoptera physalus) are also caught in nets but far less frequently. The timing of these entrapments corresponds with the spawning season for capelin (Mallotus villosus) on the beaches around the province. The magnitude and implications of this problem, both to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…(2003) reported that minke whales tend to occur mainly over the continental shelves along the shore, based on the analysis of spatial and temporal distribution patterns in this area. This distribution pattern of minke whales is probably related to the distribution pattern of prey species (Perkins and Beamish 1979, Kim et al . 2004, Kim 2008).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(2003) reported that minke whales tend to occur mainly over the continental shelves along the shore, based on the analysis of spatial and temporal distribution patterns in this area. This distribution pattern of minke whales is probably related to the distribution pattern of prey species (Perkins and Beamish 1979, Kim et al . 2004, Kim 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Although a number of studies have reported entanglements in a variety of species of whales (Perkins and Beamish 1979, Kraus 1990, Alverson et al . 1994, Knowlton and Kraus 2001, Read et al .…”
mentioning
confidence: 99%
“…These can also be both indirect and significant. For example, an inshore shift in humpback whales in Newfoundland following the crash of offshore capelin stocks led to an increase in humpback entanglements and mortalities in inshore cod traps (Lien et al, 1979;Perkins and Beamish, 1979;Whitehead and Carscadden, 1985;Lien, 1994). Kenney et al (1996) suggested a similar shift in Gulf of Maine harbor porpoise following collapse of the Georges Bank herring stock may have increased entanglements in the sink gillnet fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational activities are a major source of beach litter (Cundell, 1973;Dixon & Cooke, 1977;Nagelkerken et al, 2001;Pruter, 1987) as well as rubbish from ships at sea (Horsman, 1982;Price, Whitehall, & Bernard, 1987;Scott, 1975;. There are negative ecological effects of litter on seals (Merrell, 1980), fish and seabirds (Bourne, 1976;Day, Wehle, & Coleman, 1984;Degange & Newby, 1980;Furness, 1985;, as well as other marine mammals (Fowler, 1987;Perkins & Beamish, 1979;Shaughnessy, 1980) and turtles (Balazs, 1985). The effects include strangulation and entanglement in nets and strapping (Merrell, 1984;Wehle & Coleman, 1983), starvation and death from ingesting of plastics resulting in blockages and ulceration and/or damage to the delicate internal tissues of the stomach and intestines (Gramentz, 1988;Gregory, 1991;Laist, 1987;Wehle & Coleman, 1983), and concentration of synthetic chemicals up the food chain (Gregory, 1978;Wehle & Coleman, 1983).…”
Section: Introductionmentioning
confidence: 99%